Performance Evaluation Of Combined Code-Space Division Multiple Access With Enhanced Parallel Interference Cancellation - Odeh, Nidhal A.S. (2007)
To meet the ever growing need for wireless networks, several methods were adopted to increase the system capacity of wireless communication systems, such as Frequency Division Multiple Access (FDMA), Time Division Multiple Access (TDMA), Code Division Multiple Access (CDMA), Space Division Multiple Access (SDMA) and Orthogonal Frequency Division Multiplexing (OFDM). In this thesis, Combined Code Division Multiple Access (CDMA) and Space Division Multiple Access (SDMA) system have been investigated for capacity improvement. The analysis considered here is to evaluate the performance of combined Code-Space Division Multiple Access (C-SDMA) system. A single cell composed with one base station (BS) and N classes of users is considered. In heterogeneous environment each user class is supported by one of the different media with specific data rates and minimum required quality of service. In this thesis, the synchronous uplink channel transmission is investigated in order to detect the received signal (bits) in a combined C-SDMA system with perfect power control, with and without interference cancellation. Parallel interference cancellation (PIC) as a suboptimal multiuser detection (MUD) was employed after the matched filter (MF) receiver. The performance of the C-SDMA systems was evaluated in terms of bit error rate (BER) and user capacity, considering all the transmitted bits from other interferer users. Additionally, some asymptotic behaviour of the combined system was analyzed at high and low signal-to-noise and interference ratio (SNIR) for the desired user. Comparison between the pure CDMA and combined C-SDMA systems is done in terms of system performance with and without interference cancellation. By using limited number of available spreading codes, a novel code assignment algorithm is proposed to maintain the maximum orthogonality among users. These codes are stored in a central pool (BS) and maintained as follows. When a new user requests for a channel, the BS first checks the available signatures in terms of codes and Angle of Arrival (AoA); it then assigns the user with an already used code (used by other users) if they are spatially orthogonal to each other, otherwise an available new code will be assigned. If all codes are already utilized then the user will be blocked. Finally, the probability of blocking was evaluated in terms of various numbers of available codes. Matlab was used as the simulation software throughout this thesis. The results obtained showed that the combined C-SDMA system improve the performance by about 4 dB gain over the pure CDMA system at BER of 10-1. On the other hand the system gains 5 dB in the combined C-SDMA system with PIC receiver over the receiver without PIC at BER of 10-4. Hence, it is apparent that the combined C-SDMA system with PIC is able to accommodate more users than the other systems. Finally,the code assignment algorithm is able to further enhance the system capacity by utilizing the same resources compared to the fixed code assignment strategy. In this case, the probability of blocking can be decreased substantially by adding few numbers of additional spreading codes in the system.